2018
DOI: 10.21608/jappmu.2018.41146
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Detoxification of Jojoba Meal by Aspergillus oryzae and Impact of its Utilization in Ewes and Lambs' Feeding

Abstract: The present study was conducted at Maryout Research Station, Desert Research Center, Egypt. Jojoba meal (JM) was treated biologically with Aspergllus orgyzae Fk-923 to study its effects on performance, digestibility coefficient, nutritive value, blood metabolites, and rumen characteristic of sheep. Total of 30 Barki ewes aged 3-4 years old with an average weight of 33.46 kg were randomly allotted into three experimental treatments (10 ewes of each) to study the reproductive traits of Barki sheep. The experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Adding jojoba meal to animal's ration increased nutrients digestibility, improved animal general health and viability, and enhanced the metabolic process through increasing protein anabolism and decreasing protein degradation. The study concluded that 14% treated jojoba meal with the fungus can be used in growing lambs ration (Abdou, 2018). A study was conducted to measure the effect of treating jojoba meal with Tricoderma ressie on poultry production.…”
Section: Detoxification Of Jojoba Mealsmentioning
confidence: 99%
“…Adding jojoba meal to animal's ration increased nutrients digestibility, improved animal general health and viability, and enhanced the metabolic process through increasing protein anabolism and decreasing protein degradation. The study concluded that 14% treated jojoba meal with the fungus can be used in growing lambs ration (Abdou, 2018). A study was conducted to measure the effect of treating jojoba meal with Tricoderma ressie on poultry production.…”
Section: Detoxification Of Jojoba Mealsmentioning
confidence: 99%